The literature of the violence written by women: a look from the novel ¡Viva Cristo Rey! - Martínez Rangel, Yennyfer Natalí; Montealegre Quintero, Carolina (Rastros Rostros, 2011)
The article provides an analysis of the work of Colombian novelist Silvia Galvis and it is based on the research carried out on applications of the political proposals in the twentieth century Colombian novel. This research began en la Universidad Cooperativa de Colombia, Bucaramanga, in the second semester of 2009 and it ended in the first semester of 2011. Silvia Galvis describes in her book the confrontations between liberals and conservatives, and how women have been submitted and located in the domestic and private spaces. Even if women have been in the political movements of this country, their role has been limited and the complaint born in the hands of this Santander writer